A COMPARATIVE ANALYSIS OF VIRTUAL AND TRADITIONAL LEARNING ENVIRONMENT IN PAKISTAN - Ayesha Mehboob,N. A. Sangi (PJE, 2023)
Online education is increasingly becoming common in higher education for supporting traditional education as well as emerging as an opportunity for delivering entire education online. In Online education, multimedia materials are used to support learning and the ability to adapt the course content to meet a wider range of learner interests and abilities. T